TEACHERS THEORETICAL AND PRACTICAL PROBLEMS IN APPLYING PERFORMANCE ASSESMENT IN ENGLISH LANGUAGE CLASSROOM : ITS RELEVANT IMPLEMENTATION IN ENGLISH FOR TOURISM ASSESSMENT - Dewa Gede Ngurah Byomantara (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2016)
Performance Assessment (hereafter PA) is not really new, hut it is still difficult to apply. The majority of English language teachers could not design tasks and scoring rubrics of PA well. This is a gap. Based on the theoretical and practical characteristics of PA,